Feasibility and early outcomes of laparoscopic plicated sleeve gastrectomy: a case-control study - Rogula, Tomasz (Medical Studies/Studia Medyczne, 2015)
Introduction : Sleeve gastrectomy (SG) continues to gain popularity as a viable weight loss procedure with well-documented outcomes and procedure-specific adverse effects. It has become increasingly indicated for the treatment of morbid obesity. Aim of the research : To compare a novel approach to SG, which aims to reduce SG-specific complications, to the standard SG procedure. Material and methods : Sixteen morbidly obese patients with a mean body mass index (BMI) of 48.5 kg/m 2 ± SD who underwent the novel laparoscopic plicated sleeve gastrectomy (LPSG) were retrospectively studied. The control group included 18 patients who underwent laparoscopic SG. Study and control groups were matched for BMI and gender. Study group patients underwent a partial SG with imbrication of the distal 2/3 of the staple line with 2 cm overlap and 3–4 cm of the pre-pyloric stomach. Control group SG patients had their staple line oversewn without plication. Outcomes at 3, 6 and 12 months were compared and analyzed. Results: There was no statistically significant difference in weight loss at 12 months between the LPSG and SG groups. Postoperative nausea was comparable between the two groups. No major complications were noted in either group. Conclusions: The LPSG is a modification of the standard SG which has comparable outcomes, safety and feasibility. It may lead to a decrease in unwanted complications such as sleeve stricture or obstruction. Further studies on long-term outcomes are needed to assess its value as a bariatric procedure.